Air Pollution from Cement Plants: Case Study on Particulate Matter in Bihar, India. Issue 3 (2nd July 2020) - Jena, Madhab Chandra; Mishra, Sarat kumar; Moharana, Himanshu Sekhar
Abstract: Environmental pollution and its impact is a major challenge for this age of industrialization and urbanization. It is becoming difficult to breathe fresh air in the cities and industrial areas. Both indoor and outdoor air quality is becoming worse day by day. A study has been conducted to find out the level of particulate matter concentration inside a village near to a cement plant located in Bihar, India to know the impact of the cement plant on the ambient environment. The present study clearly indicates that during night time particulate matter concentrations of the village environment were high compared to the day times. It is also observed that there is a high concentration of particulate matter in the ambient air compared to WHO air quality guideline values in both the cases(day times and night times) due to emission from the nearby cement plant. Hence this study suggests that the cement plants and other similar industries should take proper actions to maintain the air quality standard in the ambient areas.In the last part of the article some of the pollution control techniqueshas been discussed in brief which would be helpful to the industries to improve their environmental sustainability targets.